2008
DOI: 10.1177/0164027507313001
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness and Longitudinal Trajectories in Elders' Functional Status

Abstract: The purpose of this study was to examine the effects of religiousness on the trajectories of difficulties with activities of daily living (ADLs) and instrumental ADLs (IADLs) in community-dwelling older adults over a three-year period. Seven waves of data from the University of Alabama at Birmingham Study of Aging were analyzed using a hierarchical linear modeling method. The study was based on the 784 participants who completed interviews every six months between December 1999 and February 2004. Frequent reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Longitudinal studies have reported that religious attendance, in particular, decreases the risk of mortality and plays a preventive role for both physical and psychological health outcomes among older adults (Gillum, King, Obisesan, & Koenig, 2008; Idler & Kasl, 1997b; Koenig et al, 1999; Law & Sbarra, 2009; Park et al, 2008; Strawbridge, Cohen, & Shema, 2000). Recent longitudinal research utilizing rigorous statistical techniques suggests that religious attendance may offer protection against functional decline among older adults, even when controlling for health and social variables as well as initial functional status (Hybels, Blazer, George, & Koenig, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies have reported that religious attendance, in particular, decreases the risk of mortality and plays a preventive role for both physical and psychological health outcomes among older adults (Gillum, King, Obisesan, & Koenig, 2008; Idler & Kasl, 1997b; Koenig et al, 1999; Law & Sbarra, 2009; Park et al, 2008; Strawbridge, Cohen, & Shema, 2000). Recent longitudinal research utilizing rigorous statistical techniques suggests that religious attendance may offer protection against functional decline among older adults, even when controlling for health and social variables as well as initial functional status (Hybels, Blazer, George, & Koenig, 2012).…”
mentioning
confidence: 99%
“…Among older adults, attendance at religious services is associated in cross-sectional studies with fewer functional limitations (Idler & Kasl, 1997a) and longitudinally predicts less functional decline (Benjamins, 2004; Idler & Kasl, 1997b; Park et al, 2008). While these relationships between religious attendance and functional status are well-established, biological mechanisms underlying these relationships have not been identified.…”
mentioning
confidence: 99%
“…It is possible that those who perceive themselves to be physically healthy find ways to continue their patterns of religious attendance even if they have experienced objective worsening of comorbidities and/ or disability. Those who attend religious services frequently are likely to have more responsibilities and obligations within their religious congregations, which may lead them to more optimistic assessments of their own health-assessments that cohere with their motivation to continue their religious participation (Park et al, 2008). Alternatively, it may be that subjective measures of health are more sensitive to small changes in health status than are the more objective measures we included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the poor older population in Connecticut (Jarvis and Northcott 1987) concludes that religiousness and attendance was positively correlated with a reduction in mortality. Other studies find that different dimensions of religious involvement have a protective effect against a functional decline among the older population (Park et al 2008; Hybels et al 2012). The study by Park et al (2008) concludes that attending religious services is related to lower levels of functional limitations and decreases the risks of developing limitations in the instrumental activities of daily living.…”
Section: Introductionmentioning
confidence: 94%
“…Other studies find that different dimensions of religious involvement have a protective effect against a functional decline among the older population (Park et al 2008; Hybels et al 2012). The study by Park et al (2008) concludes that attending religious services is related to lower levels of functional limitations and decreases the risks of developing limitations in the instrumental activities of daily living. A similar relation has not been found for private religious practices, such as watching and listening to religious media and prayer.…”
Section: Introductionmentioning
confidence: 94%